Radar fundamentals - Faulconbridge, R. Ian (Canberra [Australian Capital Territory] : Argos Press, 2019)
This text covers the basics of radar operations and theory, provides a background into the many radar-related areas and covers the electronic warfare issues from a radar perspective. Introduction of important radar principles is combined with an explanation of the major types of radar wherever possible so that the reader becomes familiar with the principles and radar types simultaneously. We do not attempt to study specific radar systems in any depth although some example systems are illustrated to reinforce theory and concepts. We also avoid some of the more complex radar topics. The text is designed for non-technical people who require an understanding of the most important radar principles, or people with a technical background looking for a broad introduction to radar systems. Accordingly, we avoid much of the mathematical complexity inherent in the subject. Some mathematics is unavoidable and is used to explain important principles. Those with a more technical bent can delve further into the subject by referring to the endnotes listed at the end of each chapter. Specifically, this text has been developed to provide basic radar system knowledge to radar operators or those employed within radar environments. The text also supports other persons in radar-related endeavours such as the acquisition or maintenance of radar systems. In Chapter 1, a basic radar block diagram is introduced to familiarise readers with the major components of a radar system. In Chapter 2, the reader is introduced to basic pulse radar as a means of explaining some fundamental radar concepts. The concepts behind radar antennas are then discussed in Chapter 3. Chapter 4 describes a subset of the many radar displays in existence with operation radar systems. The ubiquitous radar range equation is discussed in Chapter 5 as fundamental guide to radar performance and the many tradeoffs that exist in radar design. Chapter 6 describes the Doppler effect, which is a well-known acoustic effect widely used in continuous wave radar. Pulse Doppler radar and, in particular, moving target indication radar, is described in Chapter 7 as the final example of radars that make use of the Doppler effect. Chapter 8 investigates tracking and high-resolution radar. Chapter 9 investigates techniques that provide superior range and angular resolution. Chapter 10) covers secondary surveillance radar. The radar's operating environment is described in the fourth part of the text in Chapter 11. Chapter 12 covers the electronic warfare aspects of radar operation and breaks electronic warfare into the traditional three components; electronic support, electronic attack and electronic protection. At the end of each chapter is a list of reference material that explores each topic in more detail. A set of review questions is also provided at the end of each chapter with the answers to quantitative questions provided in brackets. Three appendices are provided to support the text. Appendix A lists and expands relevant acronyms. Appendix B provides a list of common prefixes and the Greek alphabet and Appendix C explains the decibel.
Includes bibliographical references and index.
Keywords: Radar; Electronics in military engineering; Radar -- Antennas; Australian